Control of ash related problems in a large scale tangentially fired boiler using CFD modelling - Vuthaluru, Hari; Vuthaluru, Rupa (Pergamon, 2010)
The objective of this study is to develop a three-dimensional combustor model for predicting the performance of full-scale tangential fired (TF) boiler and to determine the flow patterns of the gas and coal particles, with an emphasis on formation mechanism of gas flow deviations and uneven temperature on the super-heaters, re-heaters and divisional super-heater sections of the furnace. The importance of these simulations is to identify the locations of optimum additive injection ports to achieve maximum impact of additives in the combustion process to minimize the temperature deviation and reduce ash-related issues. This study is a classic example of numerical investigation into the problem of turbulent reacting flows in large scale furnaces employed in thermal power plants for the remediation of ash deposition problems. Present work also provides an investigation of the influence of number of tripped burners on the characteristics of the flow and thermal fields. Excellent agreement between the simulation results and key boiler design values and available site operation records following full-scale trials indicate that the calculations are reliable. The results obtained from the present work are directly relevant to coal-fired utilities for not only demonstrating the effectiveness of computational fluid dynamics (CFD) based tools in combating operational issues but also provides an alternative to conventional remediation strategies.